Vesicle-based cell-free synthesis of short and long unspecific peroxygenases - Walter, Ruben Magnus; Zemella, Anne; Schramm, Marina; Kiebist, Jan; Kubick, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Unspecific peroxygenases (UPOs, EC 1.11.2.1) are fungal enzymes that catalyze the oxyfunctionalization of non-activated hydrocarbons, making them valuable biocatalysts. Despite the increasing interest in UPOs that lead to the identification thousands of putative UPOs, only few of them were successfully expressed and characterized. Currently there is no universal expression system to explore their full potential. Cell-free protein synthesis has proven to be a sophisticated technique for the synthesis of difficult to express proteins. In this work, we aimed to establish an insect-based cell-free protein synthesis (CFPS) platform to produce UPOs. CFPS relies on translationally active cell-lysates rather than on living cells. Thus, the systems parameters can be directly manipulated without having to account for cell-viability, making it highly adaptable. The insect-based lysate utilized herein contains translocationally active, ER-derived vesicles (microsomes). These microsomes were already shown to allow efficient translocation of proteins into their lumen, promoting post-translational modifications (PTMs), such as disulfide bridges and N-glycosylations. Herein the ability of a redox optimized, vesicle-based, eukaryotic CFPS system to synthesize functional UPOs, was explored. The influence of different reaction parameters as well as the influence of translocation on enzyme activity was evaluated exemplarily for UPO from Marasmius rotula and Agrocybe aegerita. The capability of the herein described CFPS-system was demonstrated by the successful synthesis of a novel UPO from Podospora anserina, thus qualifying CFPS as a promising tool for the identification and evaluation of novel UPOs and variants thereof.